2015
DOI: 10.1111/trf.13275
|View full text |Cite
|
Sign up to set email alerts
|

In a canine pneumonia model of exchange transfusion, altering the age but not the volume of older red blood cells markedly alters outcome

Abstract: Background Massive exchange-transfusion of 42-day-old red blood cells (RBCs) in a canine model of S. aureus pneumonia resulted in in vivo hemolysis with increases in cell-free hemoglobin (CFH), transferrin bound iron (TBI), non-transferrin bound iron (NTBI), and mortality. We have previously shown that washing 42-day-old RBCs before transfusion significantly decreased NTBI levels and mortality, but washing 7-day-old RBCs increased mortality and CFH levels. We now report the results of altering volume, washing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 47 publications
(123 reference statements)
0
44
2
Order By: Relevance
“…It is likely that the risk of adverse outcomes after transfusion of stored blood will depend on the underlying disease and patient subpopulation in which transfusion occurs 20,38 . In previous preclinical studies, animals with bacterial infection that were transfused with SRBCs (42-days storage in dogs and 14-days storage in mice) had a significantly increased mortality compared to those transfused with FRBCs 20,21,52,53 . In conditions where tissues are compromised by infection, inflammation or ischemia, a second injury by transfusion of blood stored for a long duration might lead to increased organ damage and lethality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is likely that the risk of adverse outcomes after transfusion of stored blood will depend on the underlying disease and patient subpopulation in which transfusion occurs 20,38 . In previous preclinical studies, animals with bacterial infection that were transfused with SRBCs (42-days storage in dogs and 14-days storage in mice) had a significantly increased mortality compared to those transfused with FRBCs 20,21,52,53 . In conditions where tissues are compromised by infection, inflammation or ischemia, a second injury by transfusion of blood stored for a long duration might lead to increased organ damage and lethality.…”
Section: Discussionmentioning
confidence: 98%
“…Although many animal and clinical studies support the theory that prolonged storage of blood leads to an increased frequency of adverse outcomes, two recent prospective clinical trials did not report a mortality or morbidity difference between critically ill patients receiving transfusions of either PRBCs stored for 7 – 10 days or PRBCs stored for 21 days 914,1621,52,53 . The last two studies did not examine patient subpopulations with comorbidities such as chronic renal disease or inflammation nor were they powered to examine patients who received transfusions with PRBCs that had been stored for longer periods, for example 30–42 days, when most red cell damage and hemolysis occurs 7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Hod and coworkers 19 further showed that transfusion of human volunteers with older compared to younger stored RBCs produces extravascular hemolysis and a fourfold or greater increase in circulating serum iron and non-transferrin-bound iron. Recent evidence from animal models of infection demonstrate that even small volumes of older transfused blood increase transferrin-bound iron, lung injury, and mortality rates, 20 presumably due to adverse effects from cell-free Hb and free iron. 18,21 Clinical studies comparing blood stored for shorter and longer duration have only partially answered the question of whether these changes impact patient outcomes.…”
mentioning
confidence: 99%
“…Avoiding transfusion of heterogeneous platelets for prophylactic use might prevent refractoriness. Interestingly, a very similar two-hit concept has been suggested for red blood cell transfusions based on dog studies: dogs with bacterial infection (first hit) receiving older red blood cells containing higher concentrations of microparticles (second hit) had a much higher risk of mortality [70, 71]. …”
Section: Platelet Quality Measures For Prophylactic Transfusionmentioning
confidence: 99%